Learning Techniques and Strategies to Produce Stand-Up Comedians - Trisna Pradita Putra (TUMATA: Journal of Arts and Cultural Management, 2025)
Comedian is a profession that has been recognized since the 18th century. Although the comedian profession has been recognized, formal education or training to become a humanist and competent comedian is still very rarely carried out. “Pecahkan” is a stand-up comedy educational institution that consistently organizes training to become a solo comedian. The success of the "Palecah" institution in providing training, of course, is supported by the right learning techniques and strategies. An effective and efficient comedy education model will play an important role in producing comedians who are ethical, competent, and ready to enter the industrial world. Structured education for prospective comedians is highly necessary, considering the numerous cases of legal actions against comedians who are deemed to have offended and demeaned certain parties. This research was conducted to map the comedy education techniques and strategies carried out by “Pecahkan”. The mapping of stand-up comedian learning techniques and strategies is expected to be able to make an important contribution to the study of human resource management, especially stand-up comedy. The method used in this study is observation, especially participatory observation. Observations were made by participating in “Tipis-Tipis Rispek #4” training, organized by the "Pecahkan" Institute. The results of this study show the effectiveness of the hybrid learning model in the comedian education process, as well as the importance of comedy learning strategies through the comedy stage laboratory.